MEMORY OF THE FUTURE? DIGITAL ARCHIVES IN PUBLIC SERVICE MEDIA - Eberwein, Tobias; Gerard-Wenzel, Corinna (AoIR Selected Papers of Internet Research, 2018)
Archives by public service media (PSM) are often regarded as an ideal instrument for creating a collective 'cultural memory', which is essential in the individualized, differentiated and polarized societies of today. Technological innovations and digitization open up new possibilities in this regard, as data can be stored and made accessible more easily. In their daily work, however, PSM archives encounter various obstacles. How do PSM across Europe deal with the digitization of audiovisual archives and what exactly are the problems and challenges that accompany this process? To answer this question, the authors conducted problem-centered interviews with journalists, members of audience relations departments, legal departments, archivists and archive managers in selected European countries (Austria, Finland, the Netherlands and the United Kingdom). In addition, selected examples of the publicly accessible archived content were analyzed and evaluated. The paper highlights tensions between personal rights and collective interests in the process of creating cultural memory: One of the main transformations in archiving that digitization has brought about is the way in which the material is publicly accessed and the proportion of the material that is publicly accessible. However, digitization has also caused significant risks, particularly with regard to the legal and ethical challenges it causes. The paper concludes with proposals for media policy.